The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jsfa.11510
|View full text |Cite
|
Sign up to set email alerts
|

Influence of strains and environmental cultivation conditions on the bioconversion of ergosterol and vitamin D2 in the sun mushroom

Abstract: BACKGROUND:The fungus Agaricus subrufescens is grown commercially in China, the USA, Brazil, Taiwan and Japan, among others. However, each country adopts a cultivation system that significantly influences the agronomical parameters and chemical composition of the harvested mushrooms. In this study, the influence of the cultivation process on the content of ergosterol and vitamin D 2 was evaluated.RESULTS: Four commercial strains of A. subrufescens (ABL 04/49, ABL CS7, ABL 18/01 and ABL 19/01) and two environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The differences in ergosterol and other nutritional and bioactive compounds depend on the species, stage of development, tissues, nutrient substrate, and microclimate [ 26 , 59 ]. Vieira Junior et al [ 39 ] showed that ergosterol biosynthesis and its bioconversion into ergocalciferol were also affected by the cultivation process in Agaricus subrufescens production, showing differences between field culture and controlled conditions. Ergosterol is metabolized into a prohormone—vitamin D. Its action is related with bone mineral metabolism and with the balance of phosphorus and calcium, related to various mechanisms such as secretion and effect of insulin, regulation of the renin–angiotensin–aldosterone system, endothelial function, cell cycle control and apoptosis, immunological self-tolerance, and immune response against infections, among other effects [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in ergosterol and other nutritional and bioactive compounds depend on the species, stage of development, tissues, nutrient substrate, and microclimate [ 26 , 59 ]. Vieira Junior et al [ 39 ] showed that ergosterol biosynthesis and its bioconversion into ergocalciferol were also affected by the cultivation process in Agaricus subrufescens production, showing differences between field culture and controlled conditions. Ergosterol is metabolized into a prohormone—vitamin D. Its action is related with bone mineral metabolism and with the balance of phosphorus and calcium, related to various mechanisms such as secretion and effect of insulin, regulation of the renin–angiotensin–aldosterone system, endothelial function, cell cycle control and apoptosis, immunological self-tolerance, and immune response against infections, among other effects [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ergosterol was quantified after extraction following Vieira Junior et al [ 39 ]. It was determined by high-performance liquid chromatography (HPLC) coupled to a UV detector (280 nm), as described by Cardoso et al [ 40 ], and was identified and quantified by comparison with the pure chemical standard and expressed in mg/100g dw.…”
Section: Methodsmentioning
confidence: 99%
“…The inoculums were prepared following the methodology proposed by Vieira Junior and co-authors [18], using sorghum seeds that were boiled at 100°C for 30 minutes and then added with 2% limestone. To spawn poduction, the following steps were used: selection of mushroom and production of subculture; parent spawn; and finally grain spawn.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, ergosterol (73–90 mg/100 g) was isolated from AbM lipid fractions by Takaku et al (2001) . Ergosterol, as a precursor of vitamin D 2 (1.95–3.68 mg/100g), was usually present in AbM mushrooms at higher levels than other crops ( Rózsa et al, 2019 ; Vieira Junior et al, 2021 ). Normally, fat accounted for 1.82 g/100 g (2–8%) of the AbM ( Carneiro et al, 2013 ; Firenzuoli et al, 2008 ).…”
Section: Nutritional Values Of Abmmentioning
confidence: 99%